Study of force loss of orthodontic elastomeric chains in the laboratory - Aiman Shaddoud; T F Kosyreva (RUDN Journal of Medicine, 2016)
Objective: to assess force degradation over time of four commercially available orthodontic elastomeric chains (Ormco, Dentaurum, 3M Unitek and G & H). Methods: The synthetic elastics were submerged in 37 °C synthetic saliva and stretched on the instrument at a distance of 30 mm. With a dynamometer, the delivered force was evaluated at different intervals: at baseline, after 1 hour, 1 day, 4 days 7 days, 14 days, 21 days and 28 days. The results were subjected to ANOVA and Tukey’s test. The results showed that the elastomeric chains “Ormco” develop the least loss of power in all time tests (to 31.5% after 7 days, up to 35.1% after 28 days). At the same time, the elastomeric “Dentaurum” chain showed the highest percentage of strength loss (47.14% after 7 days, 58.57% after 28 days). No statically significant difference was found in force loss between«3M Unitek» and «G & H» elastomeric chains.